Extracellular Vesicles From Notch Activated Cardiac Mesenchymal Stem Cells Promote Myocyte Proliferation and Neovasculogenesis - Xuan, Wanling; Khan, Mahmood; Ashraf, Muhammad (Frontiers in Cell and Developmental Biology, 2020)
Cardiac mesenchymal stem cells (C-MSCs) are a novel mesenchymal stem cell (MSC) subpopulation derived from cardiac tissue, which are reported to be responsible for cardiac regeneration. Notch signaling is believed to aid in cardiac repair following myocardial injury. In this study, we have investigated the role of extracellular vesicles (EVs) from Notch1 engineered C-MSCs on angiogenesis and cardiomyocyte (CM) proliferation in ischemic myocardium. C-MSCs were isolated from Notch1flox mice (C-MSCNotch1 FF). Notch1 gene deletion was accomplished by adenoviral vector-mediated Cre recombination, and Notch1 overexpression was achieved by overexpression of Notch1 intracellular domain (N1ICD). EVs were isolated by using the size exclusion column method. Proteomic composition of EV was carried out by mass spectrometry. A mouse myocardial infarction (MI) model was generated by permanent left anterior descending (LAD) coronary artery ligation. Intramyocardial transplantation of Notch1 knockout C-MSCs (C-MSCsNotch1 KO) did not have any effect on cardiac function and scar size. On the other hand, transplantation of N1ICD-overexpressing C-MSCs (C-MSCsN1ICD) showed significant improvement in cardiac function and attenuation of fibrosis as compared to the control (PBS) group and non-modified C-MSC groups. C-MSCsN1ICD differentiated into smooth muscle cells and formed new vessels. Proteomics profiling identified several proteins, such as lysyl oxidase homolog-2 and biglycan, as highly enriched proteins in EV-C-MSCsN1ICD. Go term analysis indicated that EV-C-MSCsN1ICD were enriched with bioactive factors, potent pro-repair proteins responsible for cell migration and proliferation. EV-C-MSCsNotch1FF and EV-C-MSCsN1ICD were strongly proangiogenic under both in vitro and in vivo conditions. EV-C-MSCsN1ICD caused dense tube formation in vitro and increased neovasculogenesis in the peri-infarct area in vivo. Furthermore, EV-C-MSCsN1ICD attenuated endothelial cell (EC) and CM apoptosis under oxidative stress and ischemic injury. Similarly, EV-C-MSCNotch1 FF and EV-C-MSCN1ICD treatment improved cardiac function and decreased fibrosis in mice post-MI. EV-C-MSCsN1ICD were very effective in improving cardiac function and decreasing fibrosis. Notch1 signaling is a strong stimulus for cardiac regeneration by C-MSCs. EVs secreted by Notch1-overexpressing C-MSCs were highly effective in preventing cell death, promoting angiogenesis and CM proliferation, and restoring cardiac function post-MI. Overall, these results suggest that Notch1 overexpression may further enhance the effectiveness of EVs secreted by C-MSCs in cell-free therapy.